Elaboración de titeres para estimular el desarrollo socio-afectivo en los niños de 5 a 6 años de la Escuela República de Argentina del paralelo “B” de la provincia de Pichincha cantón Quito parroquia Amaguaña durante el periodo 2014 -2015 - Navarrete Guanotoa, Karina Mariana (2015)
This project undertakes research has been done on the Establishment of Educational unit First Basic Education "Mixed School Republic of Argentina" with the theme Development of puppets to stimulate socio-affective development in children of 5-6 years is from this it begins with data collection on the history, origin of the puppets in the world and in our country; also its importance in education; thus being able to implement it as a teaching resource active in educational planning, a study of a means of processing and handling of puppets made, was adapted to the use and environment of each child, allowing participation according to their abilities and creativity; educators were prepared and updated in the proper use of puppets making methodological guide for each topic to be addressed in his teaching puppet enrichment is the key protagonist of a good children's learning. The intention perform is implemented using the puppet as a teaching resource to be present in the classroom, the belief that the puppets are only used for the middle of the show as a mere object of distraction for children with no objective deletion namely, that allows a process of teaching.